The Relationship Between Hot-Cold Compression Therapy and Delayed Onset Muscle Soreness (DOMS) : A Comprehensive Systematic Review - Dendy Edyana; Wianne Carima (The International Journal of Medical Science and Health Research, 2026)
Introduction: Delayed Onset Muscle Soreness (DOMS) represents a common consequence of unaccustomed or intense exercise, characterized by pain, reduced function, and inflammation. Despite widespread use of thermal and compression therapies in sports recovery, the optimal application parameters and comparative effectiveness remain unclear. This systematic review evaluated the relationship between hot-cold compression therapy and DOMS outcomes. Methods: A comprehensive systematic review was conducted across multiple databases, screening studies based on predefined criteria including population (healthy individuals or athletes), intervention (thermal and/or compression therapies), outcomes (DOMS-related measures), and study design (RCTs, controlled trials, systematic reviews). Data extraction focused on intervention parameters, population characteristics, DOMS assessment methods, and primary findings. Results: Eighty studies were included, encompassing diverse interventions including contrast water therapy (CWT), cold water immersion (CWI), compression therapy, and combined approaches. CWI at 10-15°C for 10-15 minutes demonstrated consistent benefits for pain reduction (SMD -0.48 to -0.75) and functional recovery. Compression therapy, particularly pneumatic devices, improved muscle soreness (SMD -0.33) and performance measures. Combined thermal-compression approaches showed synergistic effects in some contexts (d = 0.67-1.12 for strength recovery), though not universally superior. Discussion: Intervention effectiveness demonstrated systematic variation based on temperature (optimal CWI: 10-15°C), duration (CWT optimal at 6 minutes), timing (immediate post-exercise application critical), and population (trained males show robust responses; females may respond differently). Methodological quality varied substantially, with placebo effects potentially contributing to reported benefits. Conclusion: Cold water immersion at 10-15°C for 10-15 minutes immediately post-exercise represents the most consistently beneficial single modality for DOMS, particularly in trained male athletes. Compression therapies offer viable alternatives with distinct mechanisms. Personalized approaches considering individual response patterns and resource availability are recommended over universal protocols.